Human leukocyte antigens in Turkish pediatric celiac patients - Erkan, Tülay; Kutlu, Tufan; Yılmaz, Erkan; Çullu, Fügen; Tümay, Güngör T. (The Turkish Journal of Pediatrics, 1999)
With the aim to determine the frequency of human leukocyte antigen phenotypes of celiac disease in Turkey, thirty celiac patients fulfilling the European Society of Pediatric Gastroenterology and Nutrition criteria were included in the study. The mean age of the study population was 5.8 ± 4.3 years and of the control subjects was 32.6 ± 6.7 years.The human leukocyte antigens -A, -B, -DR and -DQ were studied serologically by micro lymphocytotoxic reaction.It was found that human leukocyte antigens A-25(10), -B8, -DR18(3) and -DQ2 were more significantly frequent in the celiac population than in the control group. Children with antigen -B8 showed a five times higher risk for celiac disease and those with antigen -DQ2 showed a nine times higher risk. It was determined that human leukocyte antigen -B4 had a protective role in celiac disease.The study suggests that the human leukocyte antigen -A25(10) is a phenotype particularly encountered in Turkish pediatric celiac patients
Keywords: human leukocyte antigen HLA types; celiac disease; Turkish children